2015
DOI: 10.1007/s00392-015-0879-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life changes in patients undergoing repeated catheter ablation for atrial fibrillation

Abstract: Improvement in QOL correlates with success of AF ablation after single and repeated PVI. Assessment of QOL pre- and post-PVI can complement ECG techniques for PVI success monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The recall period was four weeks. The SF-12v2 was previously evaluated in the US National Health and Wellness Survey in atrial fibrillation patients 27 and the questionnaire was able to show an impact of atrial fibrillation-related interventions such as a pulmonary vein isolation 28 and a percutaneous closure of the left atrial appendage. 29 Symptom burden.…”
Section: Qolmentioning
confidence: 99%
“…The recall period was four weeks. The SF-12v2 was previously evaluated in the US National Health and Wellness Survey in atrial fibrillation patients 27 and the questionnaire was able to show an impact of atrial fibrillation-related interventions such as a pulmonary vein isolation 28 and a percutaneous closure of the left atrial appendage. 29 Symptom burden.…”
Section: Qolmentioning
confidence: 99%
“…Kany et al reported a similar percentage of patients with symptom improvement or no symptoms, but no detailed assessment of QoL was performed [25]. Similarly, Pezawas et al did find similar improvements in QoL, measured by the Short-Form Health Survey (SF-12) in patients receiving first or Redo-PVI [26].…”
Section: Quality Of Life After Pulmonary Vein Isolationmentioning
confidence: 99%